2021
DOI: 10.1016/j.conx.2021.100067
|View full text |Cite
|
Sign up to set email alerts
|

Abortion service availability during the COVID-19 pandemic: Results from a national census of abortion facilities in the U.S.

Abstract: Objective This study assessed the impact of COVID-19 on abortion services in all 50 United States states and the District of Columbia. Study design ANSIRH's Abortion Facility Database is a systematic collection of data on all publicly-advertising abortion facilities in the United States, updated annually through online searches and mystery shopper phone calls. Research staff updated the database in May-August 2020, assessing the number of facilities that closed, limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Abortion measures in 2020 might have been affected by the COVID-19 pandemic. Factors include temporary changes that defined abortion as a nonessential service at the hospital, local, or jurisdiction level ( 54 , 55 ), clinic closures, and changes in practice (e.g., shift from surgical abortions to medical abortions, implementation, and uptake of telehealth) ( 56 60 ). In addition, there might have been changes in pregnancy rates because of reduced sexual activity ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abortion measures in 2020 might have been affected by the COVID-19 pandemic. Factors include temporary changes that defined abortion as a nonessential service at the hospital, local, or jurisdiction level ( 54 , 55 ), clinic closures, and changes in practice (e.g., shift from surgical abortions to medical abortions, implementation, and uptake of telehealth) ( 56 60 ). In addition, there might have been changes in pregnancy rates because of reduced sexual activity ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies evaluated the impact of COVID-19 on abortion services. [36][37][38][39][40] Tu et al showed that the pandemic was associated with increased intention of seeking induced abortion due to social factors. [38] Kaller et al [39] showed that the COVID-19 pandemic caused several disruptions to abortion service availability in India, including lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] Tu et al showed that the pandemic was associated with increased intention of seeking induced abortion due to social factors. [38] Kaller et al [39] showed that the COVID-19 pandemic caused several disruptions to abortion service availability in India, including lockdowns. To reduce in-person visit time, some clinics shifted to offering medication abortion (versus procedural) or telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…At any rate, this could mean that abortion could become extremely hard to get in at least 26 of the 50 States in the United States, marking the growing conservative radicalization of the country ( 47 ). We already see some of this happening: the pandemic has caused several disruptions to abortion service availability, including clinic closures ( 48 ) driven by unreasonable governmental requirements or bans specifically targeting abortion services (e.g., forbidding the use of telemedicine for home abortions in some States) giving rise to what we now call “the politics of abortion exceptionalism” ( 49 ).…”
Section: Discussionmentioning
confidence: 99%